Marine biogenic emissions of benzene and toluene and their contribution to secondary organic aerosols over the polar oceans - Wohl, Charel; Li, Qinyi; Cuevas, Carlos Alberto; Fernandez, Rafael Pedro; Yang, Mingxi; Saiz López, Alfonso; Simó, Rafel (Science Advances)
Reactive trace gas emissions from the polar oceans are poorly characterized, even though their effects on atmospheric chemistry and aerosol formation are crucial for assessing current and preindustrial aerosol forcing on climate. Here, we present seawater and atmospheric measurements of benzene and toluene, two gases typically associated with pollution, in the remote Southern Ocean and the Arctic marginal ice zone. Their distribution suggests a marine biogenic source. Calculated emission fluxes were 0.023 ± 0.030 (benzene) and 0.039 ± 0.036 (toluene) and 0.023 ± 0.028 (benzene) and 0.034 ± 0.041 (toluene) μmol m−2 day−1 for the Southern Ocean and the Arctic, respectively. Including these average emissions in a chemistry-climate model increased secondary organic aerosol mass concentrations only by 0.1% over the Arctic but by 7.7% over the Southern Ocean, with transient episodes of up to 77.3%. Climate models should consider the hitherto overlooked emissions of benzene and toluene from the polar oceans. Fil: Wohl, Charel. Consejo Superior de Investigaciones Científicas. Instituto de Ciencias del Mar; España Fil: Li, Qinyi. Consejo Superior de Investigaciones Científicas. Instituto de Química Física; España Fil: Cuevas, Carlos Alberto. Consejo Superior de Investigaciones Científicas. Instituto de Química Física; España Fil: Fernandez, Rafael Pedro. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Interdisciplinario de Ciencias Básicas. - Universidad Nacional de Cuyo. Instituto Interdisciplinario de Ciencias Básicas; Argentina Fil: Yang, Mingxi. No especifíca; Fil: Saiz López, Alfonso. Consejo Superior de Investigaciones Científicas. Instituto de Química Física; España Fil: Simó, Rafel. Consejo Superior de Investigaciones Científicas. Instituto de Ciencias del Mar; España